Analysis of allelic pattern across milk trait genes in native cattle adapted to high altitude region of Leh-Ladakh - SODHI, MONIKA; VERMA, PREETI; BHARTI, VIJAY K; KUMAR, PRABHAT; GIRI, ARUP; K, PARVESH; GAGOI, DEEPAK; SHARMA, ANKITA; MANN, SANDEEP; MUKESH, MANISHI (The Indian Journal of Animal Sciences, 2021)
Ladakhi, the native cattle from Ladakh region of India have developed over the years under natural selection and can survive well at extreme climatic conditions, viz. high altitude, huge barren lands, low temperature (≤–20°C) and hypoxic conditions. Even at extreme survival conditions, this cattle provides around 2–5 kg of milk. This highly evolved germplasm might possess unique alleles or combinations of alleles, hence attempt was made to study the frequency of allelic variants at important candidate gene loci affecting dairy traits. The observed distribution pattern of allele frequencies were different from taurine but in accordance with other Indian native cattle breeds indicating maintenance of indicine characteristics and near absence of taurine influence/introgression effect on this naturally evolved germplasm. Further, variant E at κ-CN locus and two novel variants at BTN-3 loci were also observed. The present findings helped to understand the unique Ladakhi cattle population with respect to polymorphism and distribution of various alleles in candidate genes related to milk traits.